POPULATION CHARACTERISTICS OF MUD CRAB (Scylla serrata) IN THE WATERS OF KENDARI BAY AND SURROUNDING AREAS - Ali Suman; Ap'idatul Hasanah; Khairul Amri; Andina Ramadhani Putri Pane; Pratiwi Lestari (Indonesian Fisheries Research Journal, 2018)
The high market demand for mud crabs (Scylla serrata) has caused intensive fishing for this resources and tended to threaten their sustainability. Studies of population characteristics are the main bases for formulating management measures for sustainable utilization. The purpose of this study was to determine the population characteristics of mud crabs in the waters of Kendari Bay and its surrounding waters. The study was conducted from January to November 2016 using survey method. The study results revealed that the mud crab growth pattern in Kendari Bay was negative allometric and that the ratio of males and females was imbalance. The length at first maturity (Lm) was at a carapace width of 109.8 mm. The growth rate (K) was 1.01 per year and the maximum carapace width (L) was 206 mm. The estimated total mortality rate (Z), fishing mortality rate (F), and natural mortality rate (M) were 3.20 per year, 2.17 per year, and 1.03 per year, respectively. The exploitation rate (E) was 0.68 per year. Therefore, the exploitation rate had reached 136%, which is categorized as overfishing. In order to ensure the sustainability of the mud crabs, there is needed to apply the precautionary approach, such as reducing fishing effort by 36% of the current situation.